Socialization of the person in the context of social pedagogy - Smirnova, Ye.S.; Panchenko, A.V.; Smirnova, M.A. (KSU Publ., 2017)
The article discusses the mechanism of formation of the personality in terms of social pedagogy. Personality in social pedagogy is understood as a social phenomenon. Focus on social in personality — the key in the hands of the social teacher. The authors analyze the process of human socialization and prove that its formation as a person comes into interaction with the environment, which plays a key role in this process. This process is directed by society, through the influence of the state on certain age, social and professional group of people. Social adaptation is a prerequisite and the result of successful socialization. Young generation adopts modern system of knowledge, norms, attitudes and behavior patterns in general carried out in a social environment. In the process analyzing the different social phenomena, the authors identify important social and educational phenomena. Socio-pedagogical processes mean a variety of social phenomena and reflect the essence of pedagogical interaction of the elements of society and the individual in the various stages of its socialization. On the basis of theoretical research conducted in the article argues that social and pedagogical processes are the product of interaction between the pedagogical resources and capabilities of society and the individual in the process of socialization.
Əлеуметтік педагогика аясында тұлғаны əлеуметтендіру
Социализация личности в контексте социальной педагогики
Keywords: socialization; person; social pedagogy; social upbringing; personality upbringing; society; system of social relationships; social microenvironment; process of personality formation; social-pedagogical activity